Proteomic analysis of human lacrimal and tear fluid in dry eye disease. Issue 1 (December 2017) - Jung, Jae; Ji, Yong; Hwang, Ho; Oh, Jae; Kim, Hyun; Lee, Hyung; Kim, Kwang
Abstract To understand the pathophysiology of dry eye disease (DED), it is necessary to characterize proteins in the ocular surface fluids, including tear fluid (TF) and lacrimal fluid (LF). There have been several reports of TF proteomes, but few proteomic studies have examined LF secreted from the lacrimal gland (LG). Therefore, we characterized the proteins constituting TF and LF by liquid chromatography mass spectrometry. TF and LF were collected from patients with non-Sjögren syndrome DED and from healthy subjects. Through protein profiling and label-free quantification, 1165 proteins from TF and 1448 from LF were identified. In total, 849 proteins were present in both TF and LF. Next, candidate biomarkers were verified using the multiple reaction monitoring assay in both TF and LF of 17 DED patients and 17 healthy controls. As a result, 16 marker proteins were identified (fold-change > 1.5, p -value < 0.05), of which 3 were upregulated in TF and 8 up- and 5 down-regulated in LF. In conclusion, this study revealed novel DED markers originating from the LG and tears by in-depth proteomic analysis and comparison of TF and LF proteins.